A novel model for identifying the vessel collision risk of anchorage. (May 2020) - Liu, Zihao; Wu, Zhaolin; Zheng, Zhongyi
Highlights: A novel model of anchorage collision risk identification is proposed. Regional collision risk model was improved to fit the characteristics of vessels in anchorage. Safe room is proposed to represent the anchorage collision risk from a global perspective. Fuzzy logic was used to obtain the final anchorage collision risk index. AIS data of vessels in the anchorages off the coast of Shandong peninsular was used for case study. Abstract: The collision risk in the port area, especially in the anchorage area, increases gradually along with the progressive development of port traffic. This paper proposes a novel anchorage collision risk model in the identification of the collision risk of anchorage. First, the regional collision risk model was improved in order to fit the characteristics of vessels in anchorage. Second, a novel anchorage collision risk indicator was proposed based on ship domains to evaluate the collision risk of anchorage from a global perspective. Finally, the two indicators were synthesized to obtain a more accurate anchorage collision risk index. The AIS data of vessels in the anchorages off the coast of Shandong peninsula in the Northern Yellow Sea of China were used for the case studies. The results indicate that the proposed anchorage model may effectively represent the collision risk of anchorage. The proposed model may serve as reference for the safety analysis of port traffic and assist maritime surveillance operators in the collision risk monitoring of port traffic to enhance traffic safety.